1996
DOI: 10.1111/j.1440-1673.1996.tb00408.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of a provincial radiation oncology service: The first year report and its implications for future developments

Abstract: This study compares the actual first year's workload of a new radiation oncology department with that predicted, and assesses the impact of the differences, and their implications for future similar developments. The treatment records and diaries for the Geelong Hospital Radiation Oncology Department were reviewed after the first 12 months of operation (opened in June 1992). Statistics relating to the number of patients seen, number treated, diagnosis, etc., were evaluated and compared to the original estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…When considering the individual states before 1994, retreatment rates could be derived for Queensland, NSW/ACT and South Australia for 1990 and for South Australia in 1992, otherwise national re-treatment rates for the appropriate year were used. The national average re-treatment rates for the survey years were 28% (1986), 28% (1988), 28% (1990), 26.5% (1992), 20.2% (1994), 22.1% (1995), 25.0% (1997) and 22.3% (1999) (mean ± SD, 25.0 ± 3.11%). It was noted that low re-treatment rates, especially in 1994, were generally associated with the establishment of new departments, which…”
Section: Derivation Of the Proportion Of Patients Treatedmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering the individual states before 1994, retreatment rates could be derived for Queensland, NSW/ACT and South Australia for 1990 and for South Australia in 1992, otherwise national re-treatment rates for the appropriate year were used. The national average re-treatment rates for the survey years were 28% (1986), 28% (1988), 28% (1990), 26.5% (1992), 20.2% (1994), 22.1% (1995), 25.0% (1997) and 22.3% (1999) (mean ± SD, 25.0 ± 3.11%). It was noted that low re-treatment rates, especially in 1994, were generally associated with the establishment of new departments, which…”
Section: Derivation Of the Proportion Of Patients Treatedmentioning
confidence: 99%
“…Following these findings, decentralization and the establishment of extra centres was proposed for Victoria 24 and a new centre was established in Geelong. In 1996 Byram et al described a treatment rate of 50% in the Geelong area and 26% in the surrounding areas 25 . In 1987 the Super‐Specialty Services Working Party of the Standing Committee of the Health Ministers Advisory Council also recognized that existing regional variations were unsatisfactory and that a uniform 50% treatment rate was necessary 26…”
Section: Addendummentioning
confidence: 99%
“…One paper reported on a rural radiotherapy centre (Byram et al, 1996). They suggested (although did not prove) that better access exposed hidden demand.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to identify features of their practices that could be transferred to other rural areas but their results serve as an encouraging illustration of what can be achieved by some particularly motivated individuals. Byram et al (1996) reported on the setting up of a provincial radiation oncology service by reviewing treatment statistics from the first year. The main problem identified was higher than anticipated patient turnover (820 patients treated compared with 500 predicted).…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
“…1 The manuscript is descriptive and follows the pattern of similar reports from other Australasian centres. [2][3][4] The centre at Liverpool was equipped initially with a range of teletherapy treatment units and supporting simulation and planning units.While possession of a dedicated CT scanner may have been unique in 1995, this is no longer the case and other centres usually have ready access to scanners in their hospitals. The need for ownership of such equipment depends predominantly on proximity and access within the institution, with data transfer to the treatment planning system.The requirement for a local facility at Liverpool seems established, because 90% of 1329 new referrals lived in that health area.…”
mentioning
confidence: 99%